Roman Law in the Formation of Argentine Lawyers of the Eighteen Hundreds - Levaggi, Abelardo (1986)
This article examines the influence of Roman Law in the legal education of Argentine lawyers in the 19th century, addressing different key moments in its development. Initially, during the Hispanic period, it is observed how, despite the crisis of Common Law and the attempts to eliminate its teaching, Roman Law remained essential in legal practice. Then it examines how the Indiana universities and academies preserved the study of Roman and canon law as pillars of legal education. In the patriotic period, the University of Cordoba made reforms reducing the teaching of Roman Law, but maintaining its importance as the basis of civil law. For its part, the University of Buenos Aires did not initially include Roman Law courses, but its influence remained in the curriculum through other texts and civil law courses. In addition, the academies of jurisprudence required knowledge of Roman Law for the entrance exams. Finally, the article develops the crisis of higher education, the shortage of lawyers and how the creation of new chairs in universities such as Buenos Aires strengthened the role of Roman Law, consolidating its relevance in legal interpretation and the training of jurists.